Different pattern of stool and plasma gastrointestinal damage biomarkers during primary and chronic HIV infection - Pastor, Lucía (PLoS One, 2019)
INTRODUCTION: Primary HIV infection (PHI) is the initial phase after HIV acquisition characterized by high viral replication, massive inflammatory response and irreversible immune-damage, particularly at the gastrointestinal level. In this study we aimed to characterize the dynamics of gastrointestinal damage biomarkers during the different phases of HIV infection and assess their association with HIV-disease markers and their accuracy to differentiate PHI from chronic HIV infection (CHI). METHODS: PHI-individuals (n = 57) were identified as HIV-seronegative/HIV-RNA positive and were followed up for one year at the Manhiça District Hospital in Mozambique. Ten plasma and 12 stool biomarkers were quantified by Luminex or ELISA and levels were compared to CHI-naive (n = 26), CHI on antiretroviral-treatment (ART; n = 30) and HIV-uninfected individuals (n = 58). Regression models adjusted by time point were used to estimate the association of the biomarkers with HIV-disease markers. Receiver operating curves were compared for the best accuracy to distinguish PHI from CHI. RESULTS: Soluble (s)CD14 was significantly associated with the CD4/CD8 ratio (P < 0.05) and viremia levels (P < 0.0001) during PHI. Plasma zonulin and stool lactoferrin were significantly higher in PHI as compared to CHI-individuals (P < 0.05). Plasma zonulin demonstrated the best accuracy to identify PHI among HIV-infected individuals (AUC = 0.85 [95% CI 0.75–0.94]). Using a cutoff value of plasma zonulin ≥ 8.75 ng/mL the model identified PHI with 87.7% sensitivity (95% CI 76.3–94.9) and 69.2% specificity (95% CI 48.2–85.7). An adjusted multivariate model including age, plasma zonulin and sCD14 further increased the classification performance (AUC = 0.92 [95% CI 0.86–0.99]). CONCLUSIONS: While the stool biomarkers did not provide any predictive ability to distinguish PHI from CHI-individuals, plasma sCD14 and zonulin were significantly associated with HIV-disease markers and PHI identification, respectively. These inflammatory biomarkers may be useful to monitor changes in gastrointestinal integrity during HIV infection.